Effectiveness of Structured Teaching Programme on Knowledge Regarding Arterial Blood Gas Analysis among Nursing Students - Ghimire, Babita; Acharya, Anjana; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2023)
Background: Arterial blood gas (ABG) analysis measures blood pH, oxygen (O2), and carbon dioxide (CO2) levels. Normal pH is 7.35-7.45, PaO2 ranges from 70-100 mm Hg, PaCO2 is 35-45 mm Hg, and SaO2 is 93-98%. HCO3 normal value is 22-26 meq/l. This study assesses the effectiveness of a structured teaching program on arterial blood gas analysis knowledge among nursing students. Methods: A pre-experimental study with a one-group pretest-posttest design evaluated the effectiveness of a structured teaching program on Arterial Blood Gas analysis knowledge among nursing students from two Purbanchal University-affiliated colleges. Narayani Samudayik Nursing College was chosen using a probability-based simple random sampling lottery method. Enumerative sampling was employed to select respondents for the study. Results: The study found that 87% of respondents initially had an average knowledge level of arterial blood gas analysis, with 13% having adequate knowledge. After intervention, 82.6% demonstrated adequate knowledge, and 17.4% maintained an average level. Mean knowledge scores significantly increased from 67.15 to 87.7 in pretest and posttest, respectively (p